Shift current anomalous photovoltaics in a double perovskite ferroelectric - Linjie Wei; Fu Li; Yi Liu; Hongbin Zhang; Junhua Luo; Zhihua Sun (Proceedings of the National Academy of Sciences, 2026)
Ferroelectric anomalous photovoltaic (APV) effect, as a fascinating physical conceptual phenomenon, holds significant potentials for new optoelectronic device applications. However, due to the lack of knowledge on the origin and underlying mechanism of ferroelectric APV effect, substantial challenges still remain in exploring new APV-active candidate materials. The emerging shift current model, involving the transfer of photogenerated charges through the displacement of wave functions, has attracted considerable attention for its unique insights into the bulk photovoltaic effect. Here, we present strong APV properties in a high-temperature double perovskite ferroelectric (cyclohexylmethylammonium) 2 CsAgBiBr 7 , showing an extremely large above-bandgap photovoltage up to ~40 V. This figure-of-merit is far beyond its bandgap of ~2.3 eV and comparable to the state-of-art molecular ferroelectrics. Strikingly, the shift current model reveals an intrinsic correlation with Cs + cation displacement and provides an explicit explanation for the structural origin of ferroelectric APV activities. Besides, its steady-state APV photocurrent exhibits the unique light-polarization dependence, which endows remarkable polarization-sensitivity with the highest polarization ratios of ~41 among the known 2D single-phase materials. As the feasible exploration of ferroelectric APV characteristics illuminated by the shift current mechanism, this finding paves a pathway to assemble new optoelectronic smart devices.